2009
DOI: 10.2174/1874294700903010035
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Propagation of Arundinaria callosa Munro- an Edible Bamboo from Nodal Explants of Mature Plants

Abstract: A procedure for in vitro propagation of Arundinaria callosa Munro has been developed. The method allows bud-break from nodal segments containing single axillary bud on Murashige and Skoog (1962) medium supplemented with different concentrations of 6-benzylaminopurine (BAP). The early bud-break was obtained in 8.9-13.3 M BAP, within 8-15 days. The position of the node on the culm of lateral branches also affected bud-break percentage and multiplication, mid-culm nodes are the most suitable. The optimal concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 10 publications
4
12
0
1
Order By: Relevance
“…Pre-summer (March-April) and postmonsoon (September-October) resulted in moderate response of 81.33 % and 69.67 % respectively along with comparatively less contamination (23.21 % and 13.35 %, respectively). This supports the earlier observation of Das and Pal (2005) in Bambusa balcooa, and later, Devi and Sharma (2009) in another edible bamboo (Arundinaria callosa Munro). However, pre-summer appeared to be the best in terms of least phenol production together with frequency of response.…”
Section: Resultssupporting
confidence: 90%
“…Pre-summer (March-April) and postmonsoon (September-October) resulted in moderate response of 81.33 % and 69.67 % respectively along with comparatively less contamination (23.21 % and 13.35 %, respectively). This supports the earlier observation of Das and Pal (2005) in Bambusa balcooa, and later, Devi and Sharma (2009) in another edible bamboo (Arundinaria callosa Munro). However, pre-summer appeared to be the best in terms of least phenol production together with frequency of response.…”
Section: Resultssupporting
confidence: 90%
“…The growth also had a significant effect on development of the plants. These observations are consistent with earlier reports on different plant species [10]- [14], which showed that plants in greenhouse had different growth characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…Arya and Sharma, (1998); Arya and Arya, (2009) and Anand et al, (2013) reported 80-90% survival rate by using the same soil mixture in case of B. bambos. Devi and Sharma, (2009) used the similar potting mixture in case of Arundinaria callosa and reported 60-70% survival rate as well as Shood et al (2014) in Phyllostachys pubescens with 77% survival rate, Arya et al (2012) in D. hamiltonii, Mishra et al (2011) in B. tulda, Brar et al (2013) in D. membranaceus.…”
Section: Resultsmentioning
confidence: 84%
“…(Singh et al, 2000); B. edulis (Lin et al, 2004) and B. oldhamii (Lin et al, 2007). Arya and Sharma, (1998);Anand et al, (2013) and Nayak et al, (2010) investigated that the cytokinins (BAP and Kn) were effective in direct shoot induction of the axillary buds of B. bambos as well as Devi andSharma, (2009) in Arundinaria callosa, andChaudhary et al, (2004) in D. strictus. BAP has also been found to be essential for direct shoot induction in bamboo (Nadgir et al, 1984;Banik, 1987 andSaxena, 1990).…”
Section: Resultsmentioning
confidence: 99%